Dietary nanoparticles alter the composition and function of the gut microbiota in mice at dose levels relevant for human exposure. (August 2021) - Perez, Laeticia; Scarcello, Eleonora; Ibouraadaten, Saloua; Yakoub, Yousof; Leinardi, Riccardo; Ambroise, Jérôme; Bearzatto, Bertrand; Gala, Jean-Luc; Paquot, Adrien; Muccioli, Giulio G.; Bouzin, Caroline; van den Brule, Sybille; et al.
Abstract: Background: Nanotechnologies provide new opportunities for improving the safety, quality, shelf life, flavor and appearance of foods. The most common nanoparticles (NPs) in human diet are silver metal, mainly present in food packaging and appliances, and silicon and titanium dioxides used as additives. The rapid development and commercialization of consumer products containing these engineered NPs is, however, not well supported by appropriate toxicological studies and risk assessment. Local and systemic toxicity and/or disruption of the gut microbiota (GM) have already been observed after oral administration of NPs in experimental animals, but results are not consistent and doses used were often much higher than the estimated human intakes. In view of the strong evidence linking alterations of the GM to cardiometabolic (CM) diseases, we hypothesized that dietary NPs might disturb this GM-CM axis. Materials and methods: We exposed male C57BL/6JRj mice (n = 13 per dose group) to dietary NPs mixed in food pellets at doses relevant for human exposure: Ag (0, 4, 40 or 400 μg/kg pellet), SiO2 (0, 0.8, 8 and 80 mg/kg pellet) or TiO2 (0, 0.4, 4 or 40 mg/kg pellet). After 24 weeks of exposure, we assessed effects on the GM and CM health (n = 8 per dose group). The reversibility of the effects was examined after 8 additional weeks without NPs exposure (recovery period, n ≤ 5 per dose group). Results: No overt toxicity was recorded. The GM β-diversity was dose-dependently disrupted by the three NPs, and the bacterial short chain fatty acids (SCFAs) were dose-dependently reduced after the administration of SiO2 and TiO2 NPs. These effects disappeared completely or partly after the recovery period, strengthening the association with dietary NPs. We did not observe atheromatous disease or glucose intolerance after NP exposure. Instead, dose-dependent decreases in the expression of IL-6 in the liver, circulating triglycerides (TG) and urea nitrogen (BUN) were recorded after administration of the NPs. Conclusion: We found that long-term oral exposure to dietary NPs at doses relevant for estimated human intakes disrupts the GM composition and function. These modifications did not appear associated with atheromatous or deleterious metabolic outcomes. Highlights: We fed mice with Ag, SiO2 or TiO2 NPs over dose ranges relevant for human exposure. All NPs dose-dependently altered the gut microbiota composition after 24 weeks. SiO2 and TiO2 NPs dose-dependently reduced cecal short-chain fatty acid content. No atheroma or metabolic toxicity was associated with gut microbiota alterations. Most alterations were (partially) reversible after 8 weeks recovery.